Divergent adaptations of leaf functional traits to light intensity across common urban plant species in Lanzhou, northwestern China - Yang, Ketong; Chen, Guopeng; Xian, Junren; Chang, Hailong (Frontiers in Plant Science, 2023)
Abstract: Leaves are the most important photosynthetic organs in plants. Understanding the growth strategy of leaves in different habitats is crucial for elucidating the mechanisms underlying plant response and adaptation to the environment change. This study investigated the scaling relationships of the laminar area (LA), leaf fresh mass (LFM), leaf dry mass (LDM), and explored leaf nitrogen (N) and phosphorus (P) content in leaves, and the relative benefits of these pairwise traits in three common urban plants (Yulania denudata, Parthenocissus quinquefolia, and Wisteria sinensis) under different light conditions, including (full-sun and canopy-shade). The results showed that: the scaling exponent of LDM vs LA (> 1, p < 0.05) meant that the LDM increased faster than LA, and supported the hypothesis of diminishing returns. The LFM and LDM had isometric relationships in all the three species, suggesting that the leaf water content of the leaves was nearly unaltered during laminar growth. Y. denudata and W. sinensis had higher relative benefit in full-sun habitats, while the reverse was observed in P. quinquefolia. The N and P content and the N:P ratio in full-sun leaves were generally higher than those of canopy-shade leaves. The leaves of the three urban plants exhibited a shift in strategy during transfer from the canopy shaded to the sunny habitat for adapting to the lower light conditions. The response of plant leaves to the environment shapes the rich variations at the leaf level, and quantification of the relative benefits of plants in different habitats provides novel insights into the response and adaptation strategies of plants.